Molecular mechanism of feedback regulation of 17β‐estradiol on two kiss genes in the protogynous orange‐spotted grouper (Epinephelus coioides). Issue 6 (17th April 2017) - Guo, Yin; Wang, Qingqing; Li, Gaofei; He, Meng; Tang, Haipei; Zhang, Haifa; Yang, Xiaoli; Liu, Xiaochun; Lin, Haoran
Abstract : Kisspeptins are considered critical regulators in the hypothalamic‐pituitary‐gonadal axis because they can stimulate secretion of Gonadotropin‐releasing hormone in mammals, and may also mediate the feedback regulation of sex steroids in the hypothalamus. Two kiss1 paralogues ( kiss1 and kiss2 ) were identified in teleosts, hinting at their increased complexity of signaling for sex‐steroid feedback regulation. In the present study, molecular pathways by which 17β‐estradiol (E2 ) exerted feedback regulation on two kiss genes, via three types of estrogen receptors, were investigated in the protogynous orange‐spotted grouper ( Epinephelus coioides ). kiss2 expression in the brain significantly increased in ovariectomized orange‐spotted groupers, while E2 replacement in ovariectomized fish reversed these changes to levels in the sham‐surgery group; conversely, kiss1 expression did not change. Dual‐label in situ hybridization showed that kiss1 and kiss2 neurons express erα, erβ1, and erβ2, indicating that E2 may directly regulate kiss1 and kiss2 . Indeed, E2 treatment of transiently transfected HEK293T cells decreased the activity of both kiss promoters in the presence of erβ1 and erβ2 rather than erα . Further deletion and site‐directed mutagenesis of the kiss promoters indicated that kiss1 is regulated by E2 via an estrogen‐responsive element (ERE)‐dependent, classical pathway utilized by Erβ1, as well as via an Activator protein 1 (Ap1)‐dependent, non‐classical pathway utilized by Erβ2. kiss2 was also differently regulated by E2 through the Creb transcription factor, utilized by Erβ1 as well as a half‐ERE‐dependent, classical pathway utilized by Erβ2. Taken together, multiple signaling pathways in orange‐spotted grouper are clearly involved in the feedback regulation of E2 on kiss genes via different estrogen receptors.